Evaluation of the contribution of the transmembrane region to the ectodomain conformation of the human immunodeficiency virus (HIV-1) envelope glycoprotein. Issue 1 (December 2017) - Nguyen, Hanh; Madani, Navid; Ding, Haitao; Elder, Emerald; Princiotto, Amy; Gu, Christopher; Darby, Patrice; Alin, James; Herschhorn, Alon; Kappes, John; Mao, Youdong; Sodroski, Joseph
Abstract Background The human immunodeficiency virus (HIV-1) envelope glycoprotein (Env), a Type 1 transmembrane protein, assembles into a trimeric spike complex that mediates virus entry into host cells. The high potential energy of the metastable, unliganded Env trimer is maintained by multiple non-covalent contacts among the gp120 exterior and gp41 transmembrane Env subunits. Structural studies suggest that the gp41 transmembrane region forms a left-handed coiled coil that contributes to the Env trimer interprotomer contacts. Here we evaluate the contribution of the gp41 transmembrane region to the folding and stability of Env trimers. Methods Multiple polar/charged amino acid residues, which hypothetically disrupt the stop-transfer signal, were introduced in the proposed lipid-interactive face of the transmembrane coiled coil, allowing release of soluble cleavage-negative Envs containing the modified transmembrane region (TMmod ). We also examined effects of cleavage, the cytoplasmic tail and a C-terminal fibritin trimerization (FT) motif on oligomerization, antigenicity and functionality of soluble and membrane-bound Envs. Results The introduction of polar/charged amino acids into the transmembrane region resulted in the secretion of soluble Envs from the cell. However, these TMmod Envs primarily formed dimers. By contrast, control cleavage-negative sgp140 Envs lacking the transmembrane region formed soluble trimers, dimers and monomers. TMmod and sgp140 trimers were stabilized by the addition of a C-terminal FT sequence, but still exhibited carbohydrate and antigenic signatures of a flexible ectodomain structure. On the other hand, detergent-solubilized cleaved and uncleaved Envs isolated from the membranes of expressing cells exhibited "tighter" ectodomain structures, based on carbohydrate modifications. These trimers were found to be unstable in detergent solutions, but could be stabilized by the addition of a C-terminal FT moiety. The C-terminal FT domain decreased Env cleavage and syncytium-forming ability by approximately three-fold; alteration of the FT trimerization interface restored Env cleavage and syncytium formation to near-wild-type levels. Conclusion The modified transmembrane region was not conducive to trimerization of soluble Envs. However, for HIV-1 Env ectodomains that are minimally modified, membrane-anchored Envs exhibit the most native structures and can be stabilized by appropriately positioned FT domains.